Counting with barefoot critters - White, Teagan (Tundra Books, a division of Random House of Canada Limited, a Penguin Random House Company, 2016)
"What is a day of counting with Barefoot Critters? Making pancakes, helping friends, exploring, swimming, playing pirates, learning about numbers! Join this adorable cast of animal characters as they explore numbers and counting over the course of a day, having fun at all stops along the way"--Front jacket flap.